Ansible 2 cloud automation cookbook : write Ansible playbooks for AWS, Google Cloud, Microsoft Azure, and OpenStack /: write Ansible playbooks for AWS, Google Cloud, Microsoft Azure, and OpenStack. (2018) - Patawari, Aditya; Aggarwal, Vikas
No abstract available